Taḥlīl al-Akhṭa‘ aṣ-Ṣautiyyah fi Fidyuhāt al-Kalām bi al-Lugah al-`Arabiyyah `ala Qanaṭi al-Yūtūb MAPK Solo : Analysis of Phonological Errors in Arabic Speech Videos on the MAPK Solo YouTube Channel - Hafidzotun Nafiah; Tulus Musthofa; Nasiruddin (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Phonology is a field of linguistics that investigates language sounds according to their function. This research aims to analyze the phonological errors made by students when they perform Arabic speech. This research uses a research design with content analysis. To collect research data, the method used was the listening method using the free listening-speaking technique. This research shows that students' phonological errors often occur in letters whose pronunciation is similar. Among them are ع becomes ق , أ becomes, ك ض becomes ظ. Several factors as follows: 1) In Arabic, some sounds or pronunciations are not found in Indonesian; 2) Students' limitations in producing speech (vocabulary) in Arabic; 3) Influence of first language habits/mother tongue (interlingual), 4) Inability (not yet used to) pronouncing several hija'iyah letters according to the makharijul huruf, and 5) Teaching Arabic, in this case, teaching skills speak less than perfect Arabic (maharah kalam From these factors, there are several solutions including students study the makhorijul huruf first before entering learning, hold language seminars or workshops or take language tests, and evaluate the syllabus or curriculum used. Therefore, this research hopes to help teachers and students correct various types of phonological errors so that they can learn Arabic well. Keywords: Arabic, Error Analysis, Phonology